Fuel energy potential of pyrolyzed municipal solid wastes (2021)
Municipal wastes have become a menace and the recycling of these wastes has been the focus of many researches. In this study, municipal plastic wastes were converted to energy fuel using pyrolysis using a locally fabricated vacuum pyrolyzer. 6 kg of municipal plastic wastes (PP, PET and PS) were collected, grounded into chips using a knife milling machine and were fed into the pyrolyzer to undergo thermal degradation at a temperature of 500oC with holding time of 4-5 hours. The pyrolyzed oil was collected into a Pyrex condenser unit and subjected to pseudo-distillation at 100oC to obtain the volatile com-ponents. The percentage pyrolyzed oil mass yield was calculated using mass balance equation. The liquid fuel was analyzed for its physical properties using ASTM methods, while the chemical properties were characterized using FTIR and GC-MS. The pyrolytic process showed the percentage mass yield of the pyrolyzed oil for the municipal plastic wastes oil, char, and non-condensable gas as 82.0, 16.0 and 2.0%, respectively. The derived energy fuel indicated a cloud point, pour point, density and flash point of -26.0oC, -28.0oC, 0.839 g/cc, and 50.0oC and -28.0oC, -35.0oC, 0.744 g/cc, and 30.0 C for pyrolyzed oil and distillates oil, respectively. The FTIR and GC-MS results of the liquid pyrolyzed oil indicate the presence of aliphatic, alkane, alkene, and aromatic hydrocarbons of carbon number C9-C44 in the energy fuel. Physicochemical characterization of the recovered oil indicated similarities with the conventional fossil fuels. The technology has proven to be effective in solving the environmental problems.